Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Sure, let's solve the equation step by step.
The given equation is:
[tex]\[ 4x - 6 + 2x = 18 \][/tex]
1. Combine like terms on the left side:
We have two terms involving [tex]\( x \)[/tex]: [tex]\( 4x \)[/tex] and [tex]\( 2x \)[/tex]. Adding these together, we get:
[tex]\[ (4x + 2x) - 6 = 18 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 6x - 6 = 18 \][/tex]
2. Isolate the variable term:
To isolate the term involving [tex]\( x \)[/tex], we need to get rid of the constant term [tex]\(-6\)[/tex] on the left side. We do this by adding 6 to both sides of the equation:
[tex]\[ 6x - 6 + 6 = 18 + 6 \][/tex]
Simplifying, we get:
[tex]\[ 6x = 24 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
To find the value of [tex]\( x \)[/tex], we divide both sides of the equation by 6:
[tex]\[ \frac{6x}{6} = \frac{24}{6} \][/tex]
Simplifying, we get:
[tex]\[ x = 4 \][/tex]
So, the solution to the equation [tex]\( 4x - 6 + 2x = 18 \)[/tex] is:
[tex]\[ x = 4 \][/tex]
Therefore, the correct answer is:
C. [tex]\( x = 4 \)[/tex]
The given equation is:
[tex]\[ 4x - 6 + 2x = 18 \][/tex]
1. Combine like terms on the left side:
We have two terms involving [tex]\( x \)[/tex]: [tex]\( 4x \)[/tex] and [tex]\( 2x \)[/tex]. Adding these together, we get:
[tex]\[ (4x + 2x) - 6 = 18 \][/tex]
Simplifying inside the parentheses:
[tex]\[ 6x - 6 = 18 \][/tex]
2. Isolate the variable term:
To isolate the term involving [tex]\( x \)[/tex], we need to get rid of the constant term [tex]\(-6\)[/tex] on the left side. We do this by adding 6 to both sides of the equation:
[tex]\[ 6x - 6 + 6 = 18 + 6 \][/tex]
Simplifying, we get:
[tex]\[ 6x = 24 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
To find the value of [tex]\( x \)[/tex], we divide both sides of the equation by 6:
[tex]\[ \frac{6x}{6} = \frac{24}{6} \][/tex]
Simplifying, we get:
[tex]\[ x = 4 \][/tex]
So, the solution to the equation [tex]\( 4x - 6 + 2x = 18 \)[/tex] is:
[tex]\[ x = 4 \][/tex]
Therefore, the correct answer is:
C. [tex]\( x = 4 \)[/tex]
Answer:
C. x=4
Step-by-step explanation:
To solve the equation 4x - 6 + 2x = 18, follow these steps:
1. Combine like terms on the left side:
4x - 6 + 2x = 18
6x - 6 = 18
2. Add 6 to both sides to isolate the term with
6x - 6 + 6 = 18 + 6
6x = 24
Divide both sides by 6 to solve for x:
6x / 6 = 24 / 6
x=4
I hope this helps :)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.